Why are GPs treating subclinical hypothyroidism? Case note review and GP survey. - Allport, J; McCahon, D; Hobbs, F; Roberts, L (2013)
BACKGROUND: Subclinical hypothyroidism (SCHo) is a common biochemical diagnosis in older age. Evidence of impact is inconclusive and guidelines are inconsistent. With increasing numbers of thyroid function tests (TFTs) performed, GPs frequently have to make management decisions regarding this diagnosis. However, little is known about how SCHo is currently being managed in primary care. AIM: To explore management of SCHo in primary care and GP reported rationale for treatment of SCHo in older individuals. DESIGN: Descriptive study using retrospective case note review and GP survey. SETTING: Nineteen General Practices, Central England, UK. METHODS: Follow-up of a large cohort with subsequent detailed review of individuals for whom therapy had been initiated following diagnosis of SCHo. Data on practice policies, and rationale behind treatment were collected via GP questionnaire. RESULTS: Forty-two individuals were treated following identification of SCHo. Factors regarded as supporting instigation of therapy recorded by practitioners included symptoms, a positive antithyroid antibody test and history of radioiodine therapy. In all, 55% were registered at 3/19 practices suggesting significant between practice variation. Reasons for testing included chronic disease check-up (n = 14), presenting 'thyroid symptoms' (n = 5) and presenting other symptoms (n = 9). Reasons for therapy initiation were only recorded in 26 cases and included presence of symptoms, persistently high or increasing serum thyroid stimulating hormone concentration and patient request. Only 2/15 GPs reported having practice guidelines on management. CONCLUSION: Results suggest that GPs are uncertain how to interpret symptoms and TFT results in older individuals. There is considerable variation in management of SCHo between GPs with some GPs treating patients outside of all guideline recommendations.